2001
DOI: 10.1007/s004200000211
|View full text |Cite
|
Sign up to set email alerts
|

Acute health effects common during graffiti removal

Abstract: Though their average exposure to organic solvents was low, the graffiti removers reported significantly higher prevalence of unspecific symptoms such as fatigue and headache as well as irritative symptoms from the eyes and respiratory tract, compared with the controls. To prevent adverse health effects it is important to inform the workers about the health risks, and to restrict use of the most hazardous chemicals. Furthermore, it is important to develop good working practices and to encourage the use of perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 9 publications
0
19
0
3
Order By: Relevance
“…Graffiti removers exposed to mixtures of NMP and glycol ethers reported headaches and irritation to the skin, eyes, and upper airways (8). However, in a study by Åkesson & Paulsson (9), volunteers experimentally exposed to 50 mg/m 3 in an exposure chamber for 8 hours reported no such effects.…”
mentioning
confidence: 96%
“…Graffiti removers exposed to mixtures of NMP and glycol ethers reported headaches and irritation to the skin, eyes, and upper airways (8). However, in a study by Åkesson & Paulsson (9), volunteers experimentally exposed to 50 mg/m 3 in an exposure chamber for 8 hours reported no such effects.…”
mentioning
confidence: 96%
“…One study reported headache and irritation to the respiratory system and to the eyes after an occupational exposure as low as 3 mg/m 3 (Beaulieu and Schmerber, 1991). Langworth et al (2001) reported headaches and irritation to the skin and eyes and the upper airways among graffiti removers exposed to mixtures of NMP and glycol ethers. However, in another study where volunteers were experimentally exposed to NMP air levels of 50 mg/m 3 , no such effects were reported (Åkesson and Paulsson, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…E.g., NMP is used in the petrochemical industry, in the microelectronics fabrication industry and in the manufacturing of various compounds such as pigments, cosmetics, drugs and pesticides (International program on Chemical Safety, 2001). It is also used as a graffiti remover (Anundi et al, 1993 andLangworth et al, 2001) and has been investigated as a transdermal enhancer in the pharmaceutical industry (Barry and Bennett, 1987;Priborský et al, 1988).…”
Section: Introductionmentioning
confidence: 99%